Shoreless bridges : south east European writing in diaspora - Agoston-Nikolova, Elka (Studies in Slavic literature and poetics, 2010)
Exiles cross borders, become non-mainstream individuals and break through barriers of thought and experience. Forced or chosen detachment can lead to originality of vision, awareness of simultaneous dimensions - in short a writing that challenges boundaries of genre, monolingualism and national literatures. The writers of the Balkan (Slavic) diaspora offer narratives of critical reflection, strange fusions and unions, representative of the new cultural identities of contemporary Europe. This volume presents an interesting combination of original writer's essays (by Tzveta Sofronieva, Goran Ste.